Proceedings of the 3rd ACM/IEEE International Conference on Human Robot Interaction 2008
DOI: 10.1145/1349822.1349867
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional tangible user interface for controlling a robotic team

Abstract: We describe a new method for controlling a group of robots in three-dimensional (3D) space using a tangible user interface called the 3D Tractus. Our interface maps the task space into an interactive 3D space, allowing a single user to intuitively monitor and control a group of robots. We present the use of the interface in controlling a group of virtual software bots and a physical Sony AIBO robot dog in a simulated Explosive Ordnance Disposal (EOD) environment involving a bomb hidden inside of a building. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…In summary, the main findings of this study seem to support the inconclusiveness discussed in the Introduction section [12] where the authors conclude that their quantitative Human Behavior and Emerging Technologies results are inconclusive in suggesting whether our TUI approach is "better" than the non-TUI alternative. Also, we found no evidence that the tangible UI improved user efficiency or accuracy [28] [29].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In summary, the main findings of this study seem to support the inconclusiveness discussed in the Introduction section [12] where the authors conclude that their quantitative Human Behavior and Emerging Technologies results are inconclusive in suggesting whether our TUI approach is "better" than the non-TUI alternative. Also, we found no evidence that the tangible UI improved user efficiency or accuracy [28] [29].…”
Section: Discussionsupporting
confidence: 78%
“…The results showed that while both game versions were successful at improving programming self-beliefs, the tangible version was considered as more enjoyable [10]. In fact, many research approaches focus on using TUIs for educational purposes based on the assumption that they can provide hands-on experience, which may have positive learning outcomes [11][12][13][14], for instance, when manipulating 3D chemical molecules [15] or learning heart anatomy [16]. Sapounidis and Demetriadis made a comparative study of children's preferences regarding the use of a tangible and an isomorphic graphical interface to program a robot, and they concluded that the tangible interface was more attractive especially for girls, more enjoyable, and easier to be used by younger children.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Early work used a sensorloaded TUI-like model of an airplane to control the roll and pitch of a small simulated unmanned aerial vehicle (UAV) [23]. Other existing systems include one that used a simple, generic TUI implemented using the Nintendo Wiimote to navigate a robot and to control its morphology using gestures [12], and another that used an adjustable-height TUI to interact with a group of robots in three-dimensional space using a stylus and a tabletop computerized surface [18]. Perhaps the ultimate TUI for controlling a robot is the robot itself.…”
Section: Related Workmentioning
confidence: 99%
“…That is, how do users perceive and respond to touch and TUI-based interfaces, and how do they use them for interacting with a group of heterogeneous robots? This premise follows precedent (e. g. [18,23])we use in-lab simulations that focus on the interaction experience rather than task validity -placing the validity of our work in how it informs the design of real-world interfaces across a wide range of group HRI tasks.…”
Section: Introductionmentioning
confidence: 97%